Analysis of phosphate removal from aqueous solutions by hydrocalumite. Issue 45 (25th September 2016) - Son, Jeong-Woo; Kim, Jae-Hyun; Kang, Jin-Kyu; Kim, Song-Bae; Park, Jeong-Ann; Lee, Chang-Gu; Choi, Jae-Woo; Lee, Sang-Hyup
Abstract: In this study, phosphate (P) removal from aqueous solutions by hydrocalumite was investigated using batch experiments and model analyses. The maximum phosphate removal capacity was determined to be 127.53 mg P/g under the given experimental conditions (hydrocalumite dose = 0.05 g/L, initial P concentration = 2–20 mg P/L, reaction time = 24 h). Model analyses showed that the Elovich model was most suitable for describing the kinetic data, whereas the Redlich–Peterson model provided the best fits to the equilibrium data. Furthermore, phosphate removal by hydrocalumite was not sensitive to pH changes between 4.0 and 11.0. A thermodynamic analysis indicated that phosphate removal by hydrocalumite increased with a rise in temperature from 15 to 45°C, suggesting that the removal process was spontaneous and endothermic (Δ H ° = 32.05 kJ/mol, Δ S ° = 112.86 J/K/mol, Δ G ° = −0.47 to −3.86 kJ/mol). The phosphate removal capacity in stream water (5.40–17.25 mg P/g) was also lower than that in a synthetic P solution (6.86–27.51 mg P/g) under the given experimental conditions (initial P concentration = 2 mg P/L, hydrocalumite dose = 0.05–0.3 g/L, reaction time = 24 h). Such a result could possibly be ascribed to the presence of carbonate ions ( ) in the stream water, which could interfere with phosphate removal by hydrocalumite through the precipitation of calcium carbonate (CaCO3 ).